The EU Self-Surplus Puzzle: An Indication of VAT Fraud? - Martin T. Braml; Gabriel J. Felbermary (Center for Economic Studies and ifo Institute (CESifo), 2019)
The world runs a trade surplus with itself: the reported values of exports exceed the reported values of imports. This is a logically impossible but well-known empirical fact. Less well-known is the fact that, in recent years, more than 80 percent of the global surplus is a trade surplus that the EU has with itself. In this paper, we show that this EU self-surplus amounts to a striking 307 billion Euro in 2018. It persists in goods, services, and secondary income accounts. It also exists within the Euro Area, and is strongest between neighboring countries. Around the 2004 Eastern Enlargement, the EU self-surplus quadrupled. Balance of payments data from the United Kingdom appear highly distorted. We argue that these phenomena are not only due to measurement error. Rather, a large fraction of the EU's self-surplus puzzle seems related to fraud in value added tax. The resulting loss in tax income could amount to as much as 64 billion Euro per year.
Keywords: F36; F32; F24; H26; 330; missing trade; VAT fraud; statistical discrepancies; current accounts